Significance of Speech Intelligibility Assessors in Medium Classroom Using Analytical Hierarchy Process - Mokhtar Harun; Khairunnisa Mohd Yusof; Mohamad Ngasri Dimon; Puspa Inayat Khalid; Siti Zaleha Abdul Hamid (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
When there are constraints on the resources-equipment, manpower and time-to conduct speech intelligibility tests, the most reliable or significant SI assessor for many different types of rooms is always sought for. The purpose of this study was to determine the most significant speech intelligibility assessor in four medium classrooms. The speech intelligibility assessors tested were RT60, C50, D50, and STIPA. The data were acquired by means of sound recorder that recorded six Malay words spoken by a trained male speaker, in four medium classrooms.The recorded speech signals were analyzed by DIRAC software. The data of four speech intelligibility assessors have to be normalized before it can be analyzed by AHP. In conclusion, C50 has shown the most consistent prediction of speech intelligibility in all sampled classrooms. On the other hand, as the room gets larger, RT60 becomes significant for determining speech intelligibility in these sampled classrooms.